Consumer attitude and intention toward ridesharing. (17th February 2022) - Cheah, Isaac; Shimul, Anwar Sadat; Liang, Johan; Phau, Ian
ABSTRACT: This paper aims to examine the factors affecting consumer's intention to participate in the sharing economy in particular toward ridesharing services. Data were collected from UberX users in Australia (n = 278) and New Zealand (n = 295) using online survey and analysed through Structural Equation Modelling in AMOS 25. The research model is tested and compared across three studies. The results show that perceived usefulness and word-of-mouth significantly influence the consumers' attitude toward ridesharing. The results across two samples show that the positive relationship between perceived usefulness as well as word of mouth and attitude toward service innovation is moderated by the consumers' attitude toward the advertising. In addition, currently the ridesharing application ridesharing requires more effort from the users, especially those who have a lower self-efficacy or are risk adverse towards using this type of service innovation. This paper suggests ridesharing services utilise the power of the word of mouth and peer recommendations in the brand's promotional strategies. Furthermore, personalised e-guides and instructions can form part of the service user interface which would help curb the negative perception around app usage and complexity, and thus increase consumer confidence.